IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING QUIZIZZ GAME–BASED LEARNING AT JUNIOR HIGH SCHOOL - Annisa Dwi Pratiwi; Jim R. Tuna; Nurmin Samola (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study was conducted to determine whether the use of Quizizz game-based learning applications can improve students' vocabulary mastery or not, especially in SMP Negeri 6 Tondano. In conducting this research, a quantitative method with a pre-experimental design was used. The subject of this research is one of the classes, namely the ninth grade (IX) at SMP Negeri 6 Tondano, totaling 15 students. Data collection instruments were pre-test (before treatment) and post–test (after treatment). The tests were in the form of multiple-choice and matching tests. The results of this study showed that the average scores of the post–test is higher (88.33) than the mean scores of the pre-test (43.33). Based on the results of the study, it was concluded that the use of Quizizz game-based learning media was very effective and succeeded in improving students' vocabulary, especially on the meaning of words and equivalent meaning/synonyms, and making students more active and class learning more fun.